Requirements for Instilling Didactic Values Into Educational Materials in Higher Pedagogical Education - Nilufar, Jalilova (International Journal of Formal Education, 2024)
The article describes the components of didactic values used in the process of higher pedagogical education, the stages of value based didactic orientation , and the requirements for inculcating didactic values in higher education educational materials.